2014
DOI: 10.1002/lary.24638
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal approaches to infratemporal fossa tumors: A classification system and case series

Abstract: EEAs to ITF tumors are technically feasible with low risk of complications for well-selected patients. The proposed classification system is useful for anticipating potential sequelae for each approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 23 publications
1
38
0
7
Order By: Relevance
“…Trigeminal schwannomas (TSs) are the most common skull‐base schwannomas after vestibular schwannomas and account for up to 0.36% of all intracranial neoplasms and 8% of skull‐base schwannomas . Most of them develop in the Gasserian ganglion, but they can occur anywhere along the course of the trigeminal root, ganglion, and peripheral branches.…”
Section: Benign Lesionsmentioning
confidence: 99%
“…Trigeminal schwannomas (TSs) are the most common skull‐base schwannomas after vestibular schwannomas and account for up to 0.36% of all intracranial neoplasms and 8% of skull‐base schwannomas . Most of them develop in the Gasserian ganglion, but they can occur anywhere along the course of the trigeminal root, ganglion, and peripheral branches.…”
Section: Benign Lesionsmentioning
confidence: 99%
“…Taylor et al reported that the incidence of malignancy in patients with infratemporal fossa was 47.6%. 18 The incidence of malignancy in temporal fossa lesions has not been reported, as published studies have been case reports or have included a small number of patients. In this study, the incidence of malignant tumours of the temporal fossa was found to be 58%.…”
Section: Discussionmentioning
confidence: 98%
“…The endoscopic approach as the sole approach was reserved for benign tumors, while for malignant neoplasms the endoscopic approach was utilized in combination with other open approaches. The operative technique for the endoscopic endonasal approaches (EEAs) to the ITF have been previously described . EEAs to ITF tumors may include transpterygopalatine fossa approach, transmedial pterygoid plate approach, and translateral pterygoid plate approach.…”
Section: Methodsmentioning
confidence: 99%
“…The operative technique for the endoscopic endonasal approaches (EEAs) to the ITF have been previously described. 13 EEAs to ITF tumors may include transpterygopalatine fossa approach, transmedial pterygoid plate approach, and translateral pterygoid plate approach. Briefly, a medial maxillectomy is performed with inferior and middle turbinate removal, and F I G U R E 1 T2-weighted axial image of a high-grade malignant mesenchymal tumor of the right nasal cavity and sinuses and involving the infratemporal fossa posterior septectomy as necessary, which enables visualization of the maxillary sinus.…”
Section: Surgical Approachmentioning
confidence: 99%